Community-Based Recommendations to Improve Customer Turnout at a Non-Profit Grocery Store. (29th May 2020) - Daniel, Leena; Hinman, Sarah; Gunen, Bengucan; Harper, Kaitlyn; Poirier, Lisa; Gittelsohn, Joel
Abstract: Objectives: Aimed at improving healthy food access in a low-income neighborhood, the Salvation Army's first non-profit grocery store in Baltimore City has so far failed to attract a large customer base. The store averages just 140 customers daily and serves 500 unique families weekly, with an average transaction of 14. This study explored reasons for low usage from the perspective of community members and suggests solutions. Methods: Mixed-methods formative research was conducted at DMG Foods. In-depth interviews were conducted with store staff (n = 5), wholesalers (n = 3), local store non-users (n = 4), and store users (n = 9).Interviews focused on purchasing habits, observations, prices, marketing efforts, quality of food, location, and convenience. Direct observations of store operations (n = 8) and a short demographic survey of store users with loyalty cards (n = 119) and without loyalty cards (n = 33) was also completed. All in-depth interviews were coded and analyzed using ATLAS.ti v8.4.18. Results: The survey results indicated that the average amount spent at DMG Foods per loyalty customer within the last 30 days was 82. Only 11% survey respondents reported using DMG for all their grocery shopping. Reasons given for low store usage, included: (a) prices at DMG Foods are not low; (b) Non-users do not perceive DMG Foods as a food store; and (c) food quality concerns. In light of these responses, we made several recommendations, including: (a) make displays showing price differences between DMG Foods and other competitors; (b) place rebranded signs outside the store to indicate that DMG Foods is a grocery store; and (c) improve and maintain the quality of produce and meat in store. Additionally, store management should negotiate with wholesalers and distributors to obtain competitive wholesale prices. Conclusions: The results of this study will be used to inform DMG Foods and to help Salvation Army refine their non-profit grocery model as they expand it to other locations in Baltimore and across the United States. Funding Sources: Johns Hopkins University Bloomberg School of Public Health Department of International Health.